Nilai Syukur dalam Ngaruwat pada Masyarakat Kampung Cimalingping, Kabupaten Subang dan Implikasinya Bagi Pembelajaran Karakter di Sekolah Dasar - Aji Fauziana Ridwan; Mamat Supriatna (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2026)
The Ngaruwat tradition in Cimalingping Village, Sindangsari Subdistrict, Kasomalang District, Subang Regency, represents the community’s expression of gratitude to God, nature, and their ancestors for the abundance of agricultural produce and social harmony. This study employs a descriptive qualitative method with a symbolic approach to reveal the meanings of local wisdom values embedded in the Ngaruwat ritual. The findings indicate that Ngaruwat serves not merely as a ritual to ward off misfortune but also as an embodiment of spirituality, mutual cooperation (gotong royong), and ecological awareness among the people. These values reflect social and religious ethics that are relevant to be integrated into character education in elementary schools through an ethnopedagogical approach. The integration of values such as gratitude, environmental care, responsibility, and solidarity into culture-based learning modules can foster religious character, environmental awareness, and love for national cultural heritage. Thus, the Ngaruwat tradition serves as an educational medium that bridges local cultural heritage with modern character education in elementary schools.